Eugenio Barba - Turner, Jane 1960 November 21- (Routledge performance practitioners, 2004)
Eugenio Barba is one of the most important theatre practitioners working today. This guidebook provides exercises for both students and teachers, and also offers an historical perspective on European and world theatre